The arch-like plasty of the left atrium in correction of a mitral valve failure - V. V. Popov; A. A. Bolshak; V. V. Lazoryshynets (Клінічна хірургія, 2021)
Objective. Studying the possibilities of the method of the left atrium arch-like plasty while correcting of a mitral failure in combination with the left atrium dilatation.